2016
DOI: 10.1136/bmjopen-2015-010446
|View full text |Cite
|
Sign up to set email alerts
|

Associations between chronic conditions, body functions, activity limitations and participation restrictions: a cross-sectional approach in Spanish non-clinical populations

Abstract: ObjectivesTo analyse the relationships between chronic conditions, body functions, activity limitations and participation restrictions in the International Classification of Functioning, Disability and Health (ICF) framework.DesignA cross-sectional study.Setting2 geographical areas in the Autonomous Region of Aragon, Spain, namely, a rural area, Cinco Villas, and an urban area in the city of Zaragoza.Participants864 individuals selected by simple random sampling from the register of Social Security card holder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…The answer to this question is straightforward: because persons with chronic conditions experience considerable disability in daily life, ranging from problems in body functions such as problems with pain, the level of energy or muscle power, to limitations in activities such as doing housework or walking, and important restrictions in their participation in society, such as keeping a job and raising a family. This fact has been corroborated by diverse studies [ 2 , 39 ] and is also reinforced by the Global Burden of Disease Study, which overwhelmingly identified NCDs, many times chronic conditions, as the ones mostly associated to disability [ 40 ]. A recent article on disability, NCDs and health information stresses that it is very unfortunate that action plans for NCDs, and their corresponding monitoring frameworks, continue to heavily focus on mortality and to neglect the adequate measurement of both morbidity and disability [ 41 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The answer to this question is straightforward: because persons with chronic conditions experience considerable disability in daily life, ranging from problems in body functions such as problems with pain, the level of energy or muscle power, to limitations in activities such as doing housework or walking, and important restrictions in their participation in society, such as keeping a job and raising a family. This fact has been corroborated by diverse studies [ 2 , 39 ] and is also reinforced by the Global Burden of Disease Study, which overwhelmingly identified NCDs, many times chronic conditions, as the ones mostly associated to disability [ 40 ]. A recent article on disability, NCDs and health information stresses that it is very unfortunate that action plans for NCDs, and their corresponding monitoring frameworks, continue to heavily focus on mortality and to neglect the adequate measurement of both morbidity and disability [ 41 ].…”
Section: Discussionmentioning
confidence: 80%
“…People with chronic diseases face a variety of important problems in performing their every-day lives and in participating in society, being work one of the major areas affected [ 1 , 2 ]. Chronic diseases, also known as non-communicable diseases (NCDs), are defined by the World Health Organization (WHO) as diseases that are not passed from person to person, that have generally a long duration and slow progression [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These people with a severe or extreme disability will require occasional or regular assistance in their everyday life. Similarly, a study involving a Spanish population revealed that 51.5% of the elderly had moderate disability, which was significantly associated with cognitive impairment, cerebrovascular diseases, and locomotor diseases [ 41 ]. In contrast, a study conducted in the United States reported a lower incidence of disability among the elderly (25.4%) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selected individuals were double screened for disability and cognitive function by trained research assistants, and those with comprehensive assessments were included in the analysis [15]. Screening involved two stages: firstly, we selected individuals with at least one positive answer in a disability questionnaire, the WHODAS 2.0 12-item [14].…”
Section: Methodsmentioning
confidence: 99%